Human Rights in Al-Quran - Hashim Bin Johari (Universiti Sains Islam Malaysia, 2022)
Basic human right is not a weird issue in society today. It is deserved to human being regardless of their background. The subject matter of the research, are existed rights including all human need. The objective of this research to suggest Al-Qur'an as perfect reference of basic human rights and expounding limited human right settled by human being. Certainly, Al-Qur'an was revealed on them as the guider and fulfilled all human need. Allah is the creator who has revealed Al-Qur'an and he is all- known of creation. The research is made to explore human rights in Al-Qur'an subsequently propose it as master reference in providing human right applicable to all levels started from individual, society then country.